2018
DOI: 10.1002/aenm.201701940
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen from ALD‐Al2O3 in Kesterite Cu2ZnSnS4 Solar Cells: Grain Surface Passivation

Abstract: record 9.5% efficiency pure sulfide CZTS solar cell, [4] but it is still much lower than the S-Q limit and its CuInGaSe 2 (CIGS) counterpart. It has been identified that the main reason for the efficiency limitation is the open-circuit voltage (V oc ) deficit (E g /q −V oc , where q is the elemental charge) as a result of band fluctuation and nonradiative recombination. [5] In addition, unfavorable conduction band alignment, i.e., cliff-like conduction band offset, at the interface of CZTS absorber/ CdS has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 25 publications
(39 reference statements)
1
53
1
Order By: Relevance
“…After sulfurization, sulfur passivates the defects at the absorber's surface . XPS results indicate that the charged vacant Se sites‐related defects can be replaced by negatively charged S atoms (Figure ) . S and Se are electrically related, and S Se is thus considered to be an electrically neutral defect.…”
Section: Resultsmentioning
confidence: 99%
“…After sulfurization, sulfur passivates the defects at the absorber's surface . XPS results indicate that the charged vacant Se sites‐related defects can be replaced by negatively charged S atoms (Figure ) . S and Se are electrically related, and S Se is thus considered to be an electrically neutral defect.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Hao et al reported the potential passivation role of hydrogen in pure sulfide kesterite [22]. Hydrogen was introduced into the surface region of kesterite through the atomic layer deposition (ALD) of figure 3).…”
Section: Hydrogen (H)mentioning
confidence: 99%
“…This will result in the creation of internal junctions at ferroelectric domains and help in the separation of photoexcited charge carriers. At the same time, the role of grain boundaries is also worth considering for enhanced ion transport . Therefore, an improved knowledge of the fundamental ferroelectric nature of potential materials could significantly help in designing smart materials with better performance .…”
Section: Future Prospectsmentioning
confidence: 99%